Religiusitas dan Penerimaan Diri pada Penderita Diabetes Melitus - Badaria, Hesti; Astuti, Yulianti Dwi (Psikologika: Jurnal Pemikiran dan Penelitian Psikologi, 2004)
The current research is aimed at finding a correlation between religiosity and self acceptance among diabetic patients. Data were collected from 30 patients diagnosed with diabetes mellitus using questionnaire and analysed with Pearson product moment correlation. The result indicates that there is a significant correlation between religiosity and self acceptance (r = .603, p < .05). It can be said that 36% of the variance in self acceptance among diabetic patients are explained by their religiosity. Practical and future research implications are discussed.Key words: religiosity, self acceptance, diabetes mellitus